In: Computer Science
1.) Simplify the following Boolean Expression to a minimum number of literals.
(a'b' + c)(a + b + c')
a.)ab + a'b'c' + ac
b.)ac + abc + bc
c.)ac + a'b'c' + bc
d.)a'c + abc + b'c
e.)None of the above
2.) Reduce to two literals.
wxy'z + w'xz + wxyz
a.) xz
b.) x'z
c.) xz'
d.) yz
e.) None of the above
Solution:
(1)
Given,
=>Expression = (a'b' + c)(a + b + c')
The answer will be an option,
(c) ac + a'b'c' + bc
Explanation:
Simplification of expression:
=>Expression = (a'b' + c)(a + b + c')
Multiplying both terms
=>Expression = a'b'a + a'b'b + a'b'c' + ca + cb + cc'
=>Expression = a'ab' + ab'b + a'b'c' + ac + bc + cc'
We know that a'a = 0, b'b = 0 and cc' = 0
=>Expression = 0.b' + a.0 + a'b'c' + ac + bc + 0
=>Expression = a'b'c + ac + bc
=>Hence on the basis of simplified expression option (b) is correct and other options are incorrect.
(2)
Given,
=>Expression = wxy'z + w'xz + wxyz
The answer will be an option,
(a) xz
Explanation:
Simplification of expression:
=>Expression = wxy'z + w'xz + wxyz
Taking wxz common from first and third terms
=>Expression = wxz(y' + y) + w'xz
We know that y' + y = 1
=>Expression = wxz + w'xz
Taking xz common from first and second terms
=>Expression = (w + w')xz
We know that w + w' = 1
=>Expression = xz
=>Hence on the basis of simplified expression option (a) is correct and other options are incorrect.
I have explained each and every part with the help of statements attached to it.